Evaluating Sustainability – Related KPIS in Public Construction Supply Chain : An Green SCOR – AHP- Based Analysis - Hadiwantoro, Nazar; Nugroho, Rosalendro Eddy (IJOSMAS, 2025)
Public construction projects are increasingly required to integrate sustainability into supply chain performance, particularly in alignment with Sustainable Development Goal 12 on Responsible Consumption and Production. However, existing research often evaluates overall supply chain performance without prioritizing specific sustainability-related Key Performance Indicators (KPIs). This study addresses that gap by applying the Analytic Hierarchy Process (AHP) to assess the relative importance of sustainability indicators within a public construction project in Indonesia. Four KPIs were selected from the Green SCOR framework—supplier sustainability compliance, percentage of recycled materials used, waste reduction in construction, and energy consumption per unit of construction—based on their prominence in literature and validation through a focus group discussion with experts. Data were collected from 66 stakeholders, including owners, contractors, consultants, and suppliers. The AHP results indicate that supplier sustainability compliance (0.401) is the most critical KPI, followed by recycled materials usage (0.268) and waste reduction (0.253), while energy consumption (0.077) ranked lowest. These findings reflect stakeholder emphasis on governance and circularity rather than technical efficiency, diverging from studies in developed countries where energy consumption is often prioritized. This study contributes by refining Green SCOR applications in public construction, demonstrating the use of AHP for KPI prioritization, and providing practical recommendations for policymakers and project managers to embed sustainability into procurement and monitoring systems.